Toward the Development of an On-Chip Acoustic Focusing Fluorescence Lifetime Flow Cytometer - Sambrano, Jesus; Rodriguez, Felicia; Martin, John; Houston, Jessica P. (Frontiers in Physics, 2021)
Conventional flow cytometry is a valuable quantitative tool. Flow cytometers reveal physical and biochemical information from cells at a high-throughput, which is quite valuable for many biomedical, biological and diagnostic research fields. Flow cytometers range in complexity and typically provide multiparametric data for the user at rates of up to 50,000 cells measured per second. Cytometry systems are configured such that fluorescence or scattered light signals are collected per-cell, and the integrated optical signal at a given wavelength range indicates a particular cellular feature such as phenotype or morphology. When the timing of the optical signal is measured, the cytometry system becomes ‘time-resolved.’ Time-resolved flow cytometry (TRFC) instruments are capable of detecting fluorescence decay kinetics, and such measurements are consequential for Förster Resonance Energy Transfer (FRET) studies, multiplexing, and metabolic mapping, to name a few. TRFC systems are capture fluorescence lifetimes at rates of thousands of cells per-second, however the approach is challenged at this throughput by terminal cellular velocities. High flow rates limit the total number of photons integrated per-cell, reducing the reliability of the average lifetime as a cytometric parameter. In this contribution we examine a new approach to address this signal-to-noise issue. The technology merges time-resolved hardware with microfluidics and acoustics. We present an ‘acoustofluidic’ time-resolved flow cytometer so that cellular velocities can be adjusted on-the-fly with a standing acoustic wave (SAW). Our work shows that acoustic control can be combined with time-resolved features to appropriately balance the throughput with the optical signals necessary for lifetime data.